Research methods in applied linguistics a question and answer guide - Barjesterh, Hamed; Livani, Fatemeh Ahmadi (Society Publishing, 2023)
This book is a question and answer guide which provides novice researchers and practitioners to demystify the conceptual complexities associated with the certain topics of research methods in applied linguistics. We provided the intended readerships with a substantive source by which they can acquire a first hand, immediate experience in the main issues arise in the field of research in applied linguistics. The key feature of the book is its authentic treatment of a wide range of current and controversial topics dominating polemical debates defining the interlocking dimensions in research methods. The present book adopts maieutic method for teaching which is a form of cooperative argumentative dialogue between individuals, based on asking and answering questions to stimulate critical thinking and to draw out ideas and underlying presumptions overshadowing different areas of concern in applied linguistics. The Q and A approach of the of the book will promote awareness-raising reading and foster critical thinking mode among the readers. -- Provided by Publisher